Foret1, a reverse transcriptase-like sequence in the filamentous fungus Fusarium oxysporum. - Julien, J (1992)
We report here the isolation of Foret1, a repeated DNA sequence cloned from the fungal plant pathogen Fusarium oxysporum. This clone exhibits a high degree of sequence similarity with the retroviral pol genes. Sequences homologous to protease, reverse transcriptase, ribonuclease H are found in that order. The overall structure is homologous to the 'gypsy' class of LTR-retrotransposons. Its similarity to elements present in widely different organisms may result from its horizontal transmission in recent evolutionary time.